2002
DOI: 10.1002/ar.a.10008
|View full text |Cite
|
Sign up to set email alerts
|

Acute oxygen sensing in cellular models: Relevance to the physiology of pulmonary neuroepithelial and carotid bodies

Abstract: The combination of studies in native tissues and immortalised model systems during the last decade has made possible a deeper understanding of the physiology and functional morphology of arterial and airway oxygen sensors. Complementary and overlapping information from these earlier studies has allowed a detailed description of the cellular events that link decreased environmental oxygen to the release of physiologically important vasoactive transmitters. Since these basic pathways have now been defined functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…It should be noted that the large-conductance Ca 2ϩ -activated (BKCa) channel, commonly associated with the 6-TMD family, could be composed of 7 TMD. line), have been shown to be inhibited after acute hypoxia (35,36,87 (63). Moreover, it has been shown that Kv1.1, Kv4.3, and Kv9.3 mRNA expression is decreased after chronic hypoxia in VSMC (63).…”
Section: K ϩ Channel Function In Lung Epithelial Physiologymentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that the large-conductance Ca 2ϩ -activated (BKCa) channel, commonly associated with the 6-TMD family, could be composed of 7 TMD. line), have been shown to be inhibited after acute hypoxia (35,36,87 (63). Moreover, it has been shown that Kv1.1, Kv4.3, and Kv9.3 mRNA expression is decreased after chronic hypoxia in VSMC (63).…”
Section: K ϩ Channel Function In Lung Epithelial Physiologymentioning
confidence: 97%
“…Lung ability to rapidly adapt to environmental changes in PO 2 is crucial for survival. Neuroepithelial bodies (NEB) localized in the airway epithelium, arterial carotid bodies, and pulmonary smooth muscle cells are the three main PO 2 -sensing systems (35,36). These cells express several ion channels, particularly K ϩ channels that are sensitive to O 2 levels.…”
Section: K ϩ Channel Function In Lung Epithelial Physiologymentioning
confidence: 99%
“…In contrast to acidosis, hypoxia-induced inhibition of TASK channels depends on cellular integrity (38) and the cell type in which the channel is expressed [e.g., it is absent in Xenopus oocytes (267), but operates in HEK cells (156,196)]. Several indirect mechanisms have been proposed by which hypoxia influences the activity of oxygen-sensitive potassium channels.…”
Section: Chemoreception In the Carotid Bodymentioning
confidence: 99%
“…These recent data emphasize two important points: first, hTREK1 is the latest addition to the steadily increasing array of O 2 -sensitive ion channels (see Refs. 8,11,21), and second, where such channels are expressed in the CNS, it is of paramount importance to study their regulation at physiologically pertinent PO 2 levels (6).…”
mentioning
confidence: 99%